A trust infrastructure based authentication method for clustered vehicular ad hoc networks - Mirsadeghi, Fatemehsadat; Rafsanjani, Marjan Kuchaki; Gupta, Brij B. (Peer-to-peer networking and applications, 2021)
Vehicular Ad hoc Networks (VANETs) as a subset of mobile ad hoc networks which allow communication between any vehicle with other adjacent vehicles, road side units and infrastructure. In these networks, the purpose is to enhance the security, improve the management of urban and road traffic and provide services to the passenger. Due to problems such as reliability and privacy, messages that are exchanged in the network should be confidential and secure. Therefore, we need a secure topology to maintain trust, which enables the cryptographic process. In this paper, a trust based authentication method for clustered vehicular ad hoc networks is proposed. The efficient authentication method should be able to accurately detect malicious nodes and reduced delay and overhead. The main purpose of the proposed method is to create trustworthy and stable clusters that lead to the stability of the entire network. For this purpose, we estimate the trust degree of each vehicle by combining the trust between vehicles and the trust between the vehicle and Road Side Units (RSUs), and Cluster Heads (CHs) are selected based on this estimated trust degree. Cluster Heads along with verifiers are responsible for monitoring each vehicle. On the other hand, the cluster heads provide an optimal and secure route for transmitting messages. Messages are digitally signed by the sender and encrypted using a public/private key as distributed by a Trusted Authority (TA) and decrypted by the destination; so that each message contains a certificate from a trusted authority. In this identification, the sender and receiver of the message are verified and authentication will be achieved. By simulation results, it is proves that the proposed method increases the accuracy in detecting malicious nodes and the packet delivery ratio, and decreases the delay of authentication and overhead.